Reversible hydrogen sorption behaviors of the 3NaBH4-(x)YF3-(1-x)GdF3 system: The effect of double rare earth metal cations. (22nd February 2019) - Huang, Tianping; Zou, Jianxin; Zeng, Xiaoqin; Wang, Jie; Liu, Huabing; Ding, Wenjiang
Abstract: In the present work, NaBH4 based hydrogen storage materials, 3NaBH4 -(x)YF3 -(1-x)GdF3 composites, were prepared via mechanical ball milling with different values of x (2/3, 1/2, 1/3). The de-/rehydrogenation thermodynamic and kinetic behaviors of 3NaBH4 -(x)YF3 -(1-x)GdF3 composites were systematically investigated. These composites showed a single endothermal peak of hydrogen desorption even though two metal fluorides were added simultaneously into NaBH4 . All the 3NaBH4 -(x)YF3 -(1-x)GdF3 composites showed reversible hydrogen sorption ability and the best hydrogen absorption kinetics was observed in the 3NaBH4 -0.5YF3 -0.5GdF3 composite, with about 2 wt% hydrogen absorbed at 370 °C under 3.2 MPa H2 pressure in 1 h. Its hydrogen absorption kinetic behaviors were correlated closely to a First-order reaction model based on experimental results. According to the pressure-composition-temperature (PCT) tests, the reversible hydrogen storage capacity increases, and the hydrogen desorption enthalpy decreases along with more GdF3 addition. In particular, the desorption enthalpy with regard to the apparent Pauling's electronegativity (χ p ) of added metal cations can be described as Δ H d  = −2748.21χ p +3852.99 kJ/mol H2, where χ p =(x)∙χ p (Y 3+ )+(1-x)∙χ p (Gd 3+ ). This research helps us to clarify the effect of co-addition of two rare earth metal fluorides on reversible hydrogen sorption in NaBH4 . Highlights: Reversible hydrogen storage composites 3NaBH4 -(x)YF3 -(1-x)GdF3 were prepared. Thermodynamic and kinetic properties of composites with various 'x' were studied. Thermodynamics of the composites is related to the electronegativity of Gd 3+ and Y 3+ . After rehydrogenation, NaBH4, GdF3 and YF3 were all regenerated.